Strategi Peningkatan Kinerja Guru - Sungsang Dwi Ismarwanto; Muhamad Ridwan; John Chaidir (Amal Insani Foundation, 2023)
Teacher performance is a benchmark for the success of the world of education. Therefore, the role of the teacher has a strong influence on students so that learning objectives can be adequately achieved as expected, shown in their appearance, actions, and work performance. Teacher performance is determined by four factors, namely: (1) environment; (2) individual characteristics; (3) organizational characteristics; and (4) job characteristics. Principals play an important role in supervising, evaluating, and motivating to improve teacher performance.